First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations ''DAILY MAIL" EFFICIENCY EXHIBITION CONFERENCES, OLYMPIA. The People's League of Health was invited to organise the Health Conferences on the opening and second day of the Exhibition Conferences, which invitation was accepted, and the following were the official members of the League and other Medical Authorities who took part in the Conference : Thursday, 10th February, Child Welfare and Maternity Chairman: Lady BARRETT, C.B.E., M.D., M.S., B.Sc. Speakers: C.W. SALEEBY, M.D., F.R.S.E. Sir ALFRED FRIPP, K.C.V.O,, C.B., F.R.C.S. Dietetics Chairman: Prof. BAYLISS, D.Sc., F.R.S. Speakers: R.C. JEWESBURY, F.R.C.P. H. L. TIDY, F.R.C.P R. STENHOUSE WILLIAMS, M.S., L.R.C.P., L.R.C.S. Industrial Hygiene Chairman: Prof. MYERS Speakers: Prof. E. COLLIS, M.R.C.P. F. WATTS, M.A. E. FARMER, M.A. Friday, 11th February, Preventable Disease Chairman: Sir SIMS WOODHEAD, K.B.E., LL.D., M.D., F.R.C.P. Speakers: Sir HARRY BALDWIN, L.D.S., M.R.C.S. E.B. TURNER, F.R.C.S. ARTHUR LATHAM, M.R.C.P. W. HUNTER. C.B., F.R.C.P. Tuesday, 26th-28th July. INTERNATIONAL TUBERCULOSIS CONFERENCE held at Institute of Civil Engineers, Gt. George Street, Westminster. Sir Robert Philip, M.A., M.D., F.R.C.P., F.R.S., of the Medical Council of the League, was President and Chairman of the Conference. The Hon. Organiser attended as Delegate of the League. The following official members of the League addressed the Congress: Vice-President: The Marchioness of ABERDEEN AND TEMAIR Medical Council: Sir SIMS WOODHEAD, K.B.E., LL.D., M.D., F.R.C.P. ERIC PRITCHARD, M.D. Lay Council: Sir ARTHUR STANLEY LECTURING STAFF OF THE LEAGUE Causes and Contributing Causes of Physical Disease Sir GERMAN SIMS WOODHEAD, K.B.E., LL.D., M.D. E.H. STANCOMB, M.B., C.M. C.J. BOND, C.M.G., F.R.C.S. Causes and Contributing Causes of Moral Disease Rev. L. MASON. BISHOP OF BIRMINGHAM. Parentage - - Mrs. ROLFE Maternity - - MARY SCHARLIEB, C.B.E., M.D., M.S., J.P. Birthrate E.M. SLOAN CHESSER, M.B., Ch.B. C.W. SALEEBY, M.D., F.R.S.E. Child Welfare LETITIA FAIRFIELD, M.D. ERIC PRITCHARD, M.D. H. SCURFIELD, M.D., C.M., D.P.H. Housing and Child Welfare J. ROBERTSON, C.M.G., O.B.E., M.D. Housing - - Capt. R.J. REISS. Food F.R. CRIPPS, M.B., Ch.B. Prof. HALLIBURTON, M.D., LL.D., F.R.C.P., F.R.S. Sir DANIEL HALL. A.F. HURST, M.A., M.D., F.R.C.P. R.C. JEWESBURY, M.A., M.D., F.R.C.P. Prof. NOEL PATON, F.R.S., M.D., B.Sc. H.L. TIDY, M.A., M.D., F.R.C.P. 11 200/B/3/2/C693/1/71